2022
DOI: 10.1590/1980-5764-dn-2021-0116
|View full text |Cite
|
Sign up to set email alerts
|

Can the choice reaction time be modified after COVID-19 diagnosis? A prospective cohort study

Abstract: Assessment of cognitive processing speed through choice reaction time (CRT) can be an objective tool to assess cognitive functions after COVID-19 infection. Objective: This study aimed to assess CRT in individuals after acute COVID-19 infection over 1 year. Methods: We prospectively analyzed 30 individuals (male: 9, female: 21) with mild-moderate functional status after COVID-19 and 30 individuals (male: 8, female: 22) without COVID-19. Cognitive and neuropsychiatric symptoms were evaluated using the Montrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Luvizutto et al showed that choice reaction time can be decreased after COVID-19 diagnosis over 1 year, and this alteration was associated with decreased cognitive function during multiple tasks. 47 Some studies have shown that COVID-19 can also alter the brain’s functional connectivity pattern, causing brain fog and cognitive dysfunction for months after infection resolution. 11,21,48 Loss of executive function, reduced sustained attention, and slow reasoning for motor responses during everyday tasks in COVID-19 patients can lead to difficulties in performing multiple tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Luvizutto et al showed that choice reaction time can be decreased after COVID-19 diagnosis over 1 year, and this alteration was associated with decreased cognitive function during multiple tasks. 47 Some studies have shown that COVID-19 can also alter the brain’s functional connectivity pattern, causing brain fog and cognitive dysfunction for months after infection resolution. 11,21,48 Loss of executive function, reduced sustained attention, and slow reasoning for motor responses during everyday tasks in COVID-19 patients can lead to difficulties in performing multiple tasks.…”
Section: Discussionmentioning
confidence: 99%